Elevation of neuron specific enolase and brain iron deposition on susceptibility‐weighted imaging as diagnostic clues for beta‐propeller protein‐associated neurodegeneration in early childhood: Additional case report and review of the literature. Issue 2 (20th October 2015) - Takano, Kyoko; Shiba, Naoko; Wakui, Keiko; Yamaguchi, Tomomi; Aida, Noriko; Inaba, Yuji; Fukushima, Yoshimitsu; Kosho, Tomoki
Abstract : Beta‐propeller protein‐associated neurodegeneration (BPAN), also known as static encephalopathy of childhood with neurodegeneration in adulthood (SENDA), is a subtype of neurodegeneration with brain iron accumulation (NBIA). BPAN is caused by mutations in an X‐linked gene WDR45 that is involved in autophagy. BPAN is characterized by developmental delay or intellectual disability until adolescence or early adulthood, followed by severe dystonia, parkinsonism, and progressive dementia. Brain magnetic resonance imaging (MRI) shows iron deposition in the bilateral globus pallidus (GP) and substantia nigra (SN). Clinical manifestations and laboratory findings in early childhood are limited. We report a 3‐year‐old girl with BPAN who presented with severe developmental delay and characteristic facial features. In addition to chronic elevation of serum aspartate transaminase, lactate dehydrogenase, creatine kinase, and soluble interleukin‐2 receptor, she had persistent elevation of neuron specific enolase (NSE) in serum and cerebrospinal fluid. MRI using susceptibility‐weighted imaging (SWI) demonstrated iron accumulation in the GP and SN bilaterally. Targeted next‐generation sequencing identified a de novo splice‐site mutation, c.831‐1G>C in WDR45, which resulted in aberrant splicing evidenced by reverse transcriptase‐PCR. Persistent elevation of NSE and iron deposition on SWI may provide clues for diagnosis of BPAN in early childhood. © 2015 Wiley Periodicals, Inc.